Winds of change : - Bernard, John G. (Adams Press, 1995)
Provides the single most comprehensive and authoritative account of economic reform in the former communist countries. Includes an historical introduction to the theory and reality of the Soviet economy. Paper. DLC: Europe, Eastern Economic conditions.